Soil properties and fluidity of long-traveling landslides - Usuki, N.; Mizuyama, T. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value=""1":2,"2":"Better knowledge of the movement mode of fluidized landslide masses, which cause severe damage over wide areas, is very important for preventing sediment-related disasters. We analyzed a population of long- traveling landslides in Japan in terms of their travel coefficient and the conditions of the landslide mass, defining the ratio of travel distance (L2) to the original length of a landslide mass (L1) as the travel coefficient (Tr = L2/L1). After classifying long-traveling landslides by movement mode into fully fluidized and partly fluidized landslides, we found that the travel coefficient of fully fluidized landslides is roughly Tr ≥ 0.5. The grain size distributions of landslide masses suggest that the proportion of clay and silt is one factor behind a large travel coefficient. To evaluate the effect of grain size distribution on landslide travel coefficient and movement mode, we conducted soil mechanics tests on experimental soil specimens. These tests showed that soils having an intermediate grain size distribution, containing roughly equal proportions of gravel and sand, clay, and silt, have the smallest shear stress in the depth range of 10 - 15 m below the ground surface."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">Better knowledge of the movement mode of fluidized landslide masses, which cause severe damage over wide areas, is very important for preventing sediment-related disasters. We analyzed a population of long- traveling landslides in Japan in terms of their travel coefficient and the conditions of the landslide mass, defining the ratio of travel distance (L2) to the original length of a landslide mass (L1) as the travel coefficient (Tr = L2/L1). After classifying long-traveling landslides by movement mode into fully fluidized and partly fluidized landslides, we found that the travel coefficient of fully fluidized landslides is roughly Tr ≥ 0.5. The grain size distributions of landslide masses suggest that the proportion of clay and silt is one factor behind a large travel coefficient. To evaluate the effect of grain size distribution on landslide travel coefficient and movement mode, we conducted soil mechanics tests on experimental soil specimens. These tests showed that soils having an intermediate grain size distribution, containing roughly equal proportions of gravel and sand, clay, and silt, have the smallest shear stress in the depth range of 10 - 15 m below the ground surface.